Perancangan Sistem Smart Door Dengan Notifikasi Telegram - M.Eng, Ni’matul Ma’muriyah; , S.T., M.T, Andik Yulianto; Tymoden (Universitas Sari Mutiara Indonesia Medan, 2023)
With the development of IoT, security systems can now be accessed and tracked with a smartphone. One of the security system that can be used is RFID. RFID uses radio waves to read data from a microchip as identity. RFID systems work on electronic principles so they are more difficult to open than key systems. The key system is universal type so with one key can open the same door lock system. To prevent the possibility of keys being duplicated, a security system is needed that is more difficult to open and sends notifications to the owner if an attempt is made to access the door. By utilizing the RFID system and using telegram as a notification system, an RFID security system was designed which was equipped with a telegram notification system.